2011
DOI: 10.1002/cbic.201100671
|View full text |Cite
|
Sign up to set email alerts
|

Solubilized Gramicidin A as Potential Systemic Antibiotics

Abstract: Makeover of an old antibiotic: The channel‐forming toxin gramicidin A (gA) has been successfully converted into agents that selectively chase after bacterial cells. These novel D‐Lys‐containing gA mutants display potent antimicrobial activity and remarkable therapeutic indexes (>1000‐fold).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
63
1
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 57 publications
(71 citation statements)
references
References 40 publications
(14 reference statements)
3
63
1
1
Order By: Relevance
“…Nevertheless, systemic administration of gramicidin A may be possible in the near future. Chemical modification of gramicidin A has been shown to change the characteristics of the peptide enough to increase microbial targeting and/or decrease nonspecific toxicity (18,19,52,53), and encapsulation of gramicidin A within a targeted drug carriers such as nanoparticles may be a plausible method to safely deliver gramicidin A to only the tumor (54). Whether these approaches can be effectively applied to the use of gramicidin A as a novel cancer therapy is an essential area of future investigation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, systemic administration of gramicidin A may be possible in the near future. Chemical modification of gramicidin A has been shown to change the characteristics of the peptide enough to increase microbial targeting and/or decrease nonspecific toxicity (18,19,52,53), and encapsulation of gramicidin A within a targeted drug carriers such as nanoparticles may be a plausible method to safely deliver gramicidin A to only the tumor (54). Whether these approaches can be effectively applied to the use of gramicidin A as a novel cancer therapy is an essential area of future investigation.…”
Section: Discussionmentioning
confidence: 99%
“…Gramicidin A is a prototypical channel-forming ionophore that forms a 4-Å pore that can accommodate water, protons, and monovalent cations. Channel formation results in Na þ influx, K þ efflux, osmotic swelling, and cell lysis in biologic systems (18,19) and confers gramicidin A with potent antibiotic activity against gram-positive bacteria, fungi, and protozoa (20,21). We have previously demonstrated that gramicidin A is toxic to RCC cells and induces metabolic dysfunction and cellular energy depletion (22).…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, GA-S1 and GA-L exhibited a combination of regular and distorted α-helical structures with a small fraction of disordered motives (< 5%). It is worth noting that the antibiotic activity of GA-S and GA-L is associated with β-sheet and α-helical conformation, respectively [24,38,39]. Therefore, the antimicrobial potency of GA-S2 and GA-L is expected to be preserved in ethanol, while that of GA-S1 could be affected by peptide-solvent interactions.…”
Section: Electrospinning Of Pe44 and Peptide Mixturesmentioning
confidence: 99%
“…From a functional point of view, GA is well known because of its activity as bactericide [22,23], antibiotic [24], and potential therapeutic agent for different carcinomas [25][26][27][28]. In spite of its potential biomedical applications, encapsulation of GA has been scarcely studied due to the insolubility of this peptide, which represents a major limitation [19,[29][30][31].…”
Section: Introductionmentioning
confidence: 99%
“…Gramicidin A derivatives with the D-leucines at positions 10, 12 and 14 replaced by lysines have improved solubility in water and become cationic without altering the channel structure. These derivatives achieved bacterial specificity and low toxicity against mammalian cells [58].…”
Section: Bioactive Oligopeptidesmentioning
confidence: 99%